PROBLEM BASED LEARNING DENGAN METODE JIGSAW: UJI COBA PADA MAHASISWA PSIKOLOGI UNIVERSITAS BUNDA MULIA - Clara Moningka (Psibernetika, 2015)
Problem Based Learning with jigsaw model is a learning system which requiresstudents to collaborate with friends in a group to solve complex problems relating to the acquisition of knowledge.The principle of Problem Based Learning is self-regulated learning which is focusing on students (Students centered) and no longer focused on the teacher. This system is expected to be able to increase student’s motivation and achievement. Students are able to explorethe material by their own methods. This research was basically wanted to see the application of PBL with jigsaw method. This study was experimental research with a one-group posttest or after only a one-group design. This design involved a given group manipulations. This design was used because it was not possibleto randomize the subjects and divided them into the control group and the experimental group. This research was carried out for 3 months in one class. The results showed that the learning outcomes through PBL which measured with effectiveness of PBL scalewas considered less effective by students. They felttroubled with other students who did not have the motivation to learn. In this case, a preliminary study is a must; to determine the characteristics of students. The study also suggested that it is necessary to use PBL since elementary education. Keywords: Problem-based learning, Students centered, one-group posttest design, effectiveness of PBL scale